2019
DOI: 10.1111/aas.13454
|View full text |Cite
|
Sign up to set email alerts
|

Impact of norepinephrine on right ventricular afterload and function in septic shock—a strain echocardiography study

Abstract: Septic shock is defined as a subset of sepsis, characterised by, after adequate volume resuscitation, the need of vasopressors in order to maintain a normal mean arterial pressure (MAP) ≥65 mmHg. 1Myocardial dysfunction is commonly seen in sepsis also involving the right ventricle (RV). The number of studies on RV function in sepsis by conventional echocardiography is limited. Using American Society of Echocardiography criteria, 2 an RV dysfunction has been described in septic shock. 3,4 Furthermore, it was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Mild injury symptoms include redness, pain, and local tissue necrosis, while severe cases may suffer dysfunction, seriously compromising the treatment effect and the nurse-patient relationship [ 6 , 7 ]. To this end, comprehensive nursing has been identified for complication prevention of the lower extremities to potentiate the efficacy of norepinephrine; nonetheless, the expected treatment outcome is somehow compromised [ 8 , 9 ]. Previous studies have found that in the treatment of the skin radiation injury of breast cancer patients during radiotherapy [ 10 , 11 ], the collagen antibacterial functional dressing accelerated cell metabolism, promoted wound healing, relieved skin pain, and regulated the level of local inflammatory factors, which is conducive to injured skin repair.…”
Section: Introductionmentioning
confidence: 99%
“…Mild injury symptoms include redness, pain, and local tissue necrosis, while severe cases may suffer dysfunction, seriously compromising the treatment effect and the nurse-patient relationship [ 6 , 7 ]. To this end, comprehensive nursing has been identified for complication prevention of the lower extremities to potentiate the efficacy of norepinephrine; nonetheless, the expected treatment outcome is somehow compromised [ 8 , 9 ]. Previous studies have found that in the treatment of the skin radiation injury of breast cancer patients during radiotherapy [ 10 , 11 ], the collagen antibacterial functional dressing accelerated cell metabolism, promoted wound healing, relieved skin pain, and regulated the level of local inflammatory factors, which is conducive to injured skin repair.…”
Section: Introductionmentioning
confidence: 99%
“…Dalla et al described in his model with septic patients receiving norepinephrine that changes in afterload and preload i.e. an increase in systemic and pulmonary vascular resistance, impact LV EDV, but not ejection fraction or longitudinal strain [ 30 ]. The lack of changes in strain parameters in this cohort could also be explained by a lack of ability in the improvement of deformity based on longstanding LV dilatation, presence of valvular disease, and the presence of fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies have addressed this concern and assessed the cardiac effects of NE in a structured manner. 1,2 Hamzaoui et al demonstrated an inotropic effect of NE infusion in early phase of septic shock considering an improved echocardiographic profile of both the left ventricle and right ventricle (RV) function. 1 However, the understanding of the mechanisms behind an augmented ventricular performance, particularly RV, remained clouded in absence of data on preload and afterload parameters.…”
mentioning
confidence: 99%
“…The subsequent study by Dalla et al formally evaluated RV preload, afterload, and function in background of a NE infusion in septic shock. 2 The study outlined an improvement of RV function without an increase in the PVR or the RV afterload. These findings are noteworthy considering the contradictory literature on effects of NE on the pulmonary vasculature in NE-dependent vasodilatory shock, with some studies depicting an elevated PVR 3 while the more recent studies do not suggest accentuated PVR with NE in a setting of septic shock.…”
mentioning
confidence: 99%
See 1 more Smart Citation